Retinal Changes in Panic Disorder Patients - Baykara, Sema; Yildirim, Hakan; Kazgan, Asli; Tabara, Muhammed Fatih; Keles, Denizhan Danaci; Gurok, Mehmet Gurkan; Atmaca, Murad (Elsevier Ireland Ltd, 2022)
Aim: Optical coherence tomography (OCT) is a novel method that allows high resolution cross-sectional imaging of biological tissues. It was suggested that changes in the cranial structure or functions would be reflected in the retina. OCT has been an important method in the diagnosis and follow-up of diseases via morphometric or quantitative retinal measurements. Panic disorder (PD) is an anxiety disorder, where free radicals, inflammatory processes and neurotransmitter transmission disorders play a role in the etiology. The present study aimed to demonstrate neurodegeneration in PD by the comparison of PD patient and control OCT data.Material and Method: The study group included 21 PD patients who met the study criteria. The control group included 21 healthy individuals without any known psychiatric or organic disease, including eye disease, and gender-matched to the patient group. All participants underwent detailed psychiatric and eye examinations. Central macular thickness (CMT), macular volume (MV), mean and retinal nerve fiber layer thickness (RNFL), ganglion cell layer thickness (GCLT), and central choroidal thickness (CCT) were measured in both eyes of all participants with OCT. A sociodemographic data form, Clinical Global Impression Scale (CGIS), and Panic Disorder Severity Scale (PDSS) were administered to the participants.Results: In the study, it was determined that the CMT values of the PD patients were lower when compared to the controls in the OCT examination. There was a statistically significant difference between the CMT of the PD patient group and the control group; the CMT was lower in the patient group. There were no significant differences between the groups based on GCLT, RNFL superior, RNFL inferior, RNFL nasal, RNFL temporal, and CCT. There was no significant correlation between CGIS, PDSS scores and OCT measurements.Conclusion: This is the first study in the literature where patients with a PD diagnosis were analyzed based on the OCT method. OCT, which is a simple, noninvasive and relatively inexpensive method that the patient could easily adapt to during imaging, could be employed as a supplementary method in the diagnosis and follow-up of PD patients.
Keywords: Anxiety Disorders; Panic Disorder; Retina; Nerve Fibers; Tomography; Optical Coherence